Production of single W bosons at √s189 GeV and measurement of WWγ gauge couplings - Dova, María Teresa (2000)
Single W boson production in electron-positron collisions is studied with the L3 detector at LEP. The data sample collected at a centre-of-mass energy of <mtext>s</mtext><mtext>=188.7</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext> corresponds to an integrated luminosity of <mtext>176.4</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>pb</mtext>−1. Events with a single energetic lepton or two acoplanar hadronic jets are selected. Within phase-space cuts, the total cross-section is measured to be <mtext>0.53±0.12±0.03</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>pb</mtext>, consistent with the Standard Model expectation. Including our single W boson results obtained at lower s, the WWγ gauge couplings κγ and λγ are determined to be κγ=0.93±0.16±0.09 and λγ=−0.31+0.68−0.19±0.13.